Assessment of metacognition levels: A cross-sectional study among dental professionals in Pakistan - Tayyaba Nayab; Kaynat Jahangir; Ammara Chaudhry; Annam Imtiaz; Tooba Saeed; Malik Adeel Anwar (Journal of Shalamar Medical & Dental College)
Background: Metacognition plays a pivotal role in learning, particularly in dentistry, enabling individuals to effectively manage their cognitive processes and identify areas for improvement.